Examining of Lecturer Interaction, Digital Literacy, and Visual Media on Student Learning Outcomes: The Key Role of Learning Motivation as A Mediation Variable - Saaf, Arifin; Anggraini, Atika; Fauziyah, Selvi; Aziziy, Yunia Nabila; Dani, Ahmad; Qodariyah, Mamluatul (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
This study examined of lecturer interaction on students’ learning outcomes, with learning motivation serving as a mediating variable. The research employed a quantitative explanatory design using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study was conducted in the Tadris Ilmu Pengetahuan Alam (TIPA) Study Program at UIN Syekh Wasil Kediri and involved 22 fifth-semester students selected through total sampling. Data were collected using a five-point Likert-scale questionnaire measuring lecturer interaction, learning motivation, and learning outcomes. The results showed that lecturer interaction did not have a significant direct effect on students’ learning outcomes. However, lecturer interaction had a significant positive effect on learning motivation, and learning motivation significantly influenced learning outcomes. The mediation analysis further revealed that learning motivation significantly mediated the relationship between lecturer interaction and learning outcomes. These findings indicate that lecturer interaction contributes to student learning outcomes indirectly by strengthening learning motivation. The study highlights the importance of creating meaningful lecturer–student interaction in higher education as a way to foster student motivation and improve academic achievement. Therefore, efforts to enhance learning outcomes should focus not only on instructional delivery but also on building supportive and motivating academic interactions.